(untitled) (Research, Society and Development, 2022)
The objective of the study was to carry out an evaluation of the epidemiological profile of ACD in the state of Pará between the years 2016 to 2020. For this, the method used in this study was based on the use of the DATASUS database for ACD cases among the years from 2016 to 2020 using socioeconomic and regional variables in health. According to the finding, the months from July to January have high levels of ACD cases recorded, in addition to the most affected age being between 20 and 59 years old, allied mainly to the socioeconomic characteristics of the state’s population and the cultural aspects of food consumption of açaí in the region, also associated with the form of transmission that in most cases occurs in a vectorial way, in addition to the most affected area being rural, which combined with the health regions demonstrate differential political perspectives in the collection of case information and quality of care provided to the population with ACD. As a result, epidemiological research with ACD in the state reveals paradigms that are still present in the state, mainly for the neglected population such as blacks/browns, indigenous and riverine people, in addition to regional distribution conditions, investments in health and appropriate conditions for the treatment of ACD, which reveals that this situation needs debate in the state.